2019
DOI: 10.3389/fpsyg.2019.01993
|View full text |Cite
|
Sign up to set email alerts
|

Prenuclear L∗+H Activates Alternatives for the Accented Word

Abstract: Previous processing studies have shown that constituents that are prosodically marked as focus lead to an activation of alternatives. We investigate the processing of constituents that are prosodically marked as contrastive topics. In German, contrastive topics are prosodically realized by prenuclear L∗+H accents. Our study tests (a) whether prenuclear accents (as opposed to nuclear accents) are able to activate contrastive alternatives, (b) whether they do this in the same way as constituents prosodically mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 77 publications
4
32
1
Order By: Relevance
“…Similar results from a German eye-tracking study of early accents marking contrastive topics are reported by Braun and Biezma (2019).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results from a German eye-tracking study of early accents marking contrastive topics are reported by Braun and Biezma (2019).…”
Section: Discussionsupporting
confidence: 81%
“…Coming back to the theoretical question of whether intonational processing is incremental or holistic, our findings support both assumptions to some extent. Evidence that intonational processing is incremental is seen in the fact that listeners immediately integrate information from an early accent to infer the discourse status of the local referent, as has been previously claimed (Dahan et al 2002, Weber et al 2006, Ito & Speer 2006, Kurumada et al 2014, Braun & Biezma 2019. Note that listeners process early accents before knowing their status as prenuclear (followed by another accent), or nuclear, suggesting that this distinction is not relevant to intonation processing.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recall in this connection that Seeliger and Repp (2020) found that contrastive objects in exclamatives are marked with L+H * more frequently in comparison to new or given objects. This might be taken to suggest that this accent is used specifically for marking contrast(ive focus) in German, as is often assumed in the literature (for German e.g., Weber et al, 2006;Gotzner et al, 2013;Gotzner, 2014;Grice et al, 2017;Braun and Biezma, 2019;Braun et al, 2019a). However, this is not fully compatible with the finding in the present study that the proportion of L+H * is highest in the short exclamatives with a d-pronoun subject, which also had the slowest speaking rate of all exclamatives.…”
Section: Further General Prosodic Characteristics and Inter-individuacontrasting
confidence: 51%
“…This alleviates concerns about the linear position of focus, with subject focus (in Rel_NoAlt) always occurring earlier than object focus (in Rel_Alt). Moreover, there is evidence that contrastively focused subjects do activate alternatives in a similar way as contrastively focused objects do (e.g., Braun et al, 2018;Braun & Biezma, 2019).…”
Section: Discussionmentioning
confidence: 99%